Customary Practices and the Conflict with Law: Case Study of Marriage under Selected Native Laws and Customs in Nigeria - Omotuyi, Opeyemi Yetunde (ABUAD Law Journal, 2019)
Customary law is recognized as an integral part of the Nigerian legal system. Consequently, several enactments, such as the Marriage Act, Matrimonial Causes Act and Evidence Act, inter alia, identify the existence of customary law marriage in Nigeria. Even though the features of customary law marriage differ from one community to another, it is characterised by basic features whichshare peculiar similarities across various communities. Similarly, there are several practices and procedures peculiar to customary law marriage in Nigeria; these practices and procedures differ from one place to another. Even though customary law is described as a law which is generally accepted by a community as binding on them, it is noteworthy that such law is sometimes irrational, and may not always serve the best interest of society as a whole. Often times, it may be of interest to a particular group in the society at the expense of subordinating another group. This article explores some of the customary laws and practices of marriage in Nigeria. In so doing, it identifies those areas where the interests of one societal group are promoted at the expense or detriment of those of another group thereby, conflicting with major statutory provisions in Nigeria, as well as provisions of international Conventions to which Nigeria is a signatory.